Determination of Net Income of Shipping Companies: Analysis of Fuel Costs, Shipping Rates, and Shipping Routes mediated by Shipping Insurance - Atong Soekirman; Yuliantini Yuliantini; Primadi Candra Susanto; Euis Saribanon; Reni Dian Octaviani; Irwan Chairuddin (Greenation International Journal of Economics and Accounting, 2026)
This study aims to analyze the determination of net income in shipping companies in Indonesia by examining the influence of fuel costs, shipping rates, and shipping routes through the mediation of shipping insurance. Using a descriptive qualitative approach through a systematic literature study of 30 relevant articles (SINTA and Scopus), this study synthesizes various findings related to maritime financial performance for the period 2022–2025. The results of the study indicate that: 1) Fuel costs affect shipping insurance; 2) Shipping rates affect shipping insurance; 3) Shipping routes affect shipping insurance; 4) Fuel costs affect net income; 5) Shipping rates affect net income; 6) Shipping routes affect net income; 7) Shipping insurance affects net income; 8) Fuel costs affect net income through shipping insurance; 9) Shipping rates affect net income through shipping insurance; and 10) Shipping routes affect net income through shipping insurance. This research provides a strategic contribution to management in addressing market volatility and IMO 2020 regulations.